Importancia del plan de tutorías para el refuerzo académico en el área de matemáticas en los niños del 7mo año de educación general básica de la Escuela Fiscal Anexa Agustín Albán del cantón Pujilí - Silvia Mercedes, Jácome Yánez (2015)
The present work research of the following objective “Develop a tutorial tutoring to improve academic reinforcement in the area Mathematics in the children of 7th year of Basic General Education of the school “Agustín Alban” of Pujilí. How the tutoring application can optimize the academic reinforcement in the children. The inductive method was used in research in the development of the conclusions, the scientist who helped in the development of research and statistical interpretation of the data. The conclusions of the study were: students have had no good averages, the tutorials are sometimes to children who do not understand the subject, and parents do not get involved in the educational process and do not have tutorials for reinforcement knowledge. The contribution of this thesis was the development of a tutorial tutoring for academic reinforcement in the area of mathematics to help improve student learning.